Novel Blood-based Transcriptional Biomarker Panels Predict the Late-Phase Asthmatic Response - Singh, Amrit; Shannon, Casey P.; Kim, Young Woong; Yang, Chen Xi; Balshaw, Robert; Cohen Freue, Gabriela V.; Gauvreau, Gail M.; FitzGerald, J. Mark; Boulet, Louis-Philippe; O’Byrne, Paul M.; Tebbutt, Scott J. (American journal of respiratory and critical care medicine, 2018)
The allergen inhalation challenge is used in clinical trials to test the efficacy of new treatments in attenuating the late-phase asthmatic response (LAR) and associated airway inflammation in subjects with allergic asthma. However, not all subjects with allergic asthma develop the LAR after allergen inhalation. Blood-based transcriptional biomarkers that can identify such individuals may help in subject recruitment for clinical trials as well as provide novel molecular insights. To identify blood-based transcriptional biomarker panels that can predict an individual's response to allergen inhalation challenge. We applied RNA sequencing to total RNA from whole blood (n = 36) collected before and after allergen challenge and generated both genome-guided and de novo datasets: genes, gene-isoforms (University of California, Santa Cruz, UCSC Genome Browser), Ensembl, and Trinity. Candidate biomarker panels were validated using the NanoString platform in an independent cohort of 33 subjects. The Trinity biomarker panel consisting of known and novel biomarker transcripts had an area under the receiver operating characteristic curve of greater than 0.70 in both the discovery and validation cohorts. The Trinity biomarker panel was useful in predicting the response of subjects that elicited different responses (accuracy between 0.65 and 0.71) and subjects that elicit a dual response (accuracy between 0.70 and 0.75) upon repeated allergen inhalation challenges. Interestingly, the biomarker panel containing novel transcripts successfully validated compared with panels with known, well-characterized genes. These biomarker-blood tests may be used to identify subjects with asthma who develop the LAR, and may also represent members of novel molecular mechanisms that can be targeted for therapy.